Прикладний протокол обміну даними в Інтернеті речей - Мнушка, Оксана Василівна; Півнєва, Олександра Андріївна; Савченко, Володимир Миколайович (Харківський національний автомобільний-дорожній університет, 2019)
Проаналізовано застосування протоколів обміну даними в інтернеті речей. Запропоновано прикладний протокол обміну даним для пристроїв з обмеженими обчислювальними можливостями для застосування в системі збору та оброблення даних з віддалених об’єктів керування, проаналізовано структуру протоколу та перспективи його використання.

Currently, many various application protocols are used for data transfer on the Internet of Things. One of the main problems is that nonstandard protocols for various devices are used, which causes more and more problems in computational environment. Goal. The goal is development and analysis of the structure of the application protocol for the exchange of data for devices that transmit data over a computer network and have limited computing capabilities compared to other devices onthe same network. Methodology. The analytical methods of research are used for development and application of methods and devices for data transfer on the Internet of thing. Results. The protocol structure for data exchange is developed. The proposed approach allows you to get rid of redundant data when working with the same type of data (data of the same size) by masking and removing irrelevant values from the transmitted data at a given time. Originality. The developed protocol is based on the ideas of the MODBUS protocol and expands its functional resources through the implementation of mechanized techniques for removing excess information from transmitted data. Practical value. Reducing the amount of computation and cutting computations to standard operations of shift and masking can reduce the requirements for the processing power of equipment, therefore, increase the economic efficiency of development.
Application protocol of data transfer in the Internet of Things
Keywords: Internet of Things; мережний протокол; оброблення даних; network protocol; data processing